Recombinant Bacillus subtilis CM65-Patt′ is a potential feed attractant of Megalobrama amblycephala: evaluation based on appetite regulatory system, growth performance, and intestinal functions - Chu, Xiaoyu; Zhou, Jingyu; Xiong, Sisi; Ye, Beile; Liu, Zishang; Wang, Xi; Tian, Xinyi; Li, Xiangfei; Jiang, Guangzhen; Liu, Wenbin; Shi, Xiaoli; Xiang, Xiaoe; et al. (Frontiers in Marine Science, 2025)
This study was conducted to investigate the feed attractant properties of recombinant Bacillus subtilis CM65-Patt′ (secreting Patt, a functional peptide screened after enzymatic hydrolysis of the cotton meal) on the appetite regulatory system, growth performance, intestinal structure integrity, and digestive and absorptive functions of blunt snout bream (Megalobrama amblycephala). A total of 240 blunt snout breams were selected (10.85 ± 0.25 g) and divided into four groups (three replicates per group), including control group (C, basic diet), original bacteria group (OB, 1 × 108 CFU/kg Bacillus subtilis CM65) and two levels of recombinant bacteria groups (RB1, 1 × 108 CFU/kg Bacillus subtilis CM65-Patt′; RB2, 1 × 109 CFU/kg Bacillus subtilis CM65-Patt′). After a 10-week feeding trial, the results showed that the appropriate dietary Bacillus subtilis CM65-Patt′ supplementation (1 × 109 CFU/kg) enhanced appetite and increased feed intake while improving growth performance via the activation of growth hormone–insulin-like growth factor (GH–IGF) axis, enhanced intestinal absorptive capability, and maintained the integrity of intestinal structure by increasing the relative mRNA expression of tight junction proteins. Overall, those indices in the OB group had no significant change. In conclusion, this study confirmed that Bacillus subtilis CM65-Patt′ (or Patt) has great potential as a feed attractant, which can be recommended for use as a long-lasting effective feed attractant for fish.